Urinary Concentrations of Aquaporin-1 and Perilipin-2 in Patients with Renal Cell Carcinoma Correlate with Tumor Size and Stage but Not Grade - Morrissey, Jeremiah J. (2013)
OBJECTIVE: To evaluate trends in urine aquaporin-1 (AQP1) and perilipin 2 (PLIN2) concentrations in patients with clear cell and papillary renal cell carcinoma (RCC) this investigation determined the relationship between the urine concentration of these biomarkers and tumor size, grade and stage. MATERIALS AND METHODS: Biomarker concentrations were determined by sensitive and specific Western blot procedures normalized to urine creatinine excretion. Analysis included 61 patients undergoing a partial or a radical nephrectomy for clear cell or papillary renal cancer and 43 age- and sex-matched control patients. Relationships between urine biomarker concentrations and tumor size, stage, and grade were assessed. RESULTS: Patients with renal cell carcinoma had 35-fold and 9-fold higher median urinary AQP1 and PLIN2 concentrations, respectively, compared to controls (p values). Both tumor markers decreased following tumor resection, to concentrations equivalent to those of controls. The sensitivity and specificity were both 100% for AQP1, and 92% and 100% for PLIN2. There was a significant linear correlation between tumor size and prenephrectomy AQP1 (Spearman coefficient 0.78, P<0.001) and PLIN2 (Spearman coefficient 0.69, P<0.001) concentrations. There was a correlation of both markers with tumor stage (overall P=0.030), when stage was dependent primarily on tumor size (stages T1 and T2), but not with stage T3 which reflected extra-renal spread. Neither marker showed a significant correlation with tumor grade. CONCLUSIONS: AQP1 and PLIN2 are significantly increased in patients with clear cell and papillary renal cell carcinoma compared to controls. Preoperative urinary concentrations of these markers reflect tumor size and stage.